New biomarkers and therapeutic targets of human liver cancer: Transcriptomic findings. (11th August 2021) - Qin, Li; Huang, Dongning; Huang, Jian; Huang, Haixin
ABSTRACT: Hepatocellular carcinoma (HCC) is one of the most common causes of cancer‐related deaths worldwide, causing 782, 000 deaths in 2018. Poor prognosis and lack of treatment are the reasons for the high mortality rate of HCC. In the current study, we conducted a comparative transcriptomic analysis, followed by a series of bioinformatics analyses, including Gene Ontology (GO) enrichment analysis and Ingenuity Pathway Analysis (IPA), aiming to unfold the detailed molecular mechanisms underlying the development of HCC. In the comparative transcriptomic analysis of 10 pairs of HCC tumoral tissues and adjunct nontumoral tissues, we identified 115 common differentially expressed genes in HCC. The GO enrichment analysis of these genes highlighted alterations in the immune response, cell proliferation and DNA damage, energetic metabolism, cell–matrix adhesion, and filament assembly in HCC. In addition, the canonical pathway analysis of IPA further showed the importance of many cell‐signaling pathways involved in the carcinogenesis of HCC. The findings of this study provide a cluster of novel biomarkers and molecular therapeutic targets for HCC diagnosis and treatment.